Pengaruh Adopsi Digital Marketing dan Pertumbuhan Ekonomi Wilayah terhadap Peningkatan volume Penjualan UMKM di Platform E-Commerce Surabaya - Tri Wulandari Nurrisa Octhariany; Dian Chusnul Aulia; Aisyah Maisyaroh Alifah; Nindya Kartika Kusmayati; Anita Kartika Sari (Faculty of Social and Political Science, 2026)
This study aims to evaluate the impact of digital marketing adoption and regional economic growth on the sales performance of MSMEs in Surabaya. Amidst the trend of digitalization and the post-pandemic economic recovery, business actors are required to be adaptive in utilizing technology to maintain sales volume stability. This quantitative research involved 67 MSME respondents in Surabaya, selected through a purposive sampling technique. Primary data were collected using a structured questionnaire and subsequently processed using Structural Equation Modeling (SEM) via SmartPLS 4 software. The results indicate that, simultaneously, digital marketing strategies and macroeconomic conditions have a positive and significant influence on sales volume, with a variable contribution of 57.7% (R-Square 0.577). Individually, the use of e-commerce platforms was found to be the most dominant factor. These findings suggest that the acceleration of local economic growth, coupled with the digital proficiency of business actors, serves as the primary driver for increasing revenue in the MSME sector.